FEMINISME TOKOH ISTRI DALAM NOVEL PEREMPUAN ITU BERMATA SAGA KARYA AGUST DAPA LOKA (ANALISIS ISI) - Supriyati Supriyati; Aswardi Pratama (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this research is to describe and archive Feminist character in the novel Perempuan Itu Bermata Saga by Agust Dapa Loka. This research is descriptive qualitative which solves the problems by describing and interpreting the objects in the form of social phenomenon on people’s lives based on their reality. By using this kind of research, the research can describe data that are related to feminist aspects in the novel Perempuan Itu Bermata Saga by Agust Dapa Loka. The result of this research indicates that there are 45 eppressions which represent feminist aspects. There are 20 expressionswhich are related to well attitude in the novel Perempuan Itu Bermata Saga  by  Agust Dapa Loka. There are 15 expressions which are related to patience and sincere attitude. There are 10 expressions which are related to sacrifice attitude of the wife character. Based on the result of this research, it can be concluded that there are 50 expressions of feminism representation in the novel Perempuan Itu Bermata Saga  by Agust Dapa Loka and the most dominant aspect occured in the novel is sincere attitude of 20 expressions.